Inward technology transfer as an interactive process - Trott, P.; Cordey-Hayes, M.; Seaton, R.A.F.
The present paper follows the development of the scenario previously put forward by two of the three authors in Technovation, Vol. 13, no. 1 (1993). A conceptual framework is described and then applied to a number of businesses within ICI Chemicals and Polymers Ltd.
Seaton and Cordey-Hayes [1] have drawn attention to many of the limitations and deficiencies in traditional technology transfer mechanisms. They argued that this was largely due to the dominance of the linear model of innovation on conventional thinking. Furthermore, they presented an alternative model of technology transfer (accessibility-mobility-receptivity) which emphasized the interactive nature of the process and highlighted the absence of any substantial research within the area of receptivity. This paper continues from that 1993 paper and focuses on the concept of 'receptivity' in the context of inward technology transfer. A conceptual framework is developed which identifies four major components of the inward technology transfer process. These are : 'awareness', 'association', 'assimilation' and 'application'. Using this conceptual device, a series of studies is conducted within a number of businesses within ICI Chemicals and Polymers, Ltd. The conclusions indicate the importance of non-routine activities and effective communications between credible boundary-spanning individuals. These are key aspects of the assimilation of new knowledge and the inward transfer process. This requires successful organizations not only to be efficient and competitive at their routine business in order to survive in the short term, but also to make room for opportunities for these creative, non-routine assimilation processes, which are more stochastic in nature, if they are to remain competitive in the long term.
Keywords: Technology transfer; Interactive process